Dinamika Perkembangan ISHARI dan Implementasi Nilainya dalam Pembelajaran - Susilo, Tanfidzul Haqi; Jauhari, Najib (Jayapangus Press, 2024)
Local history including the art of hadrah ISHARI is increasingly forgotten by the community, especially students in the era of globalization. The art of hadrah ISHARI has its roots in the Islamic tradition of commemorating the birthday of the Prophet Muhammad. ISHARI faces the threat of existence due to shifting community preferences towards modern art. This situation reflects a lack of appreciation for values that are increasingly displaced by globalization and instant trends. This research uses a qualitative method that focuses on the implementation of ISHARI'S development dynamics and values in history learning, according to the independent curriculum. The data in this study were obtained through observation, interviews, and documentation. The main resource person is the chairman of the Jombang branch of ISHARI. This research highlights the urgency of understanding and preserving local values such as ISHARI in the context of education. With an interesting learning approach for the younger generation, it is expected to increase appreciation for local history and arts. The implementation of ISHARI values in the independent curriculum is expected to form positive characters in students and increase their understanding of local cultural heritage. The results of this study contribute to increasing public awareness, especially among students, of the importance of preserving local history and arts. The implementation of ISHARI values in the independent curriculum is a strategic step to maintain and pass on values to the younger generation.